Proceedings of the Twenty-Seventh Southeastern Symposium on System Theory
DOI: 10.1109/ssst.1995.390560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of finite difference time domain results for scattered EM fields: Yee algorithm vs. a characteristic based algorithm

Abstract: TwoJinite-direrence time-domain (FDTD) algorithms for computing scattered electromagnetic fields are compared. The Yee algorithm [IJ is compared to a characteristic-based algorithm [2] using a simple twodimensional geometry.The scattered Jields cf a conducting strip given an incident transverse magneticshort-duration Gaussian pulse are computed using both algorithms. The characteristics qf the scattered fields are compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…Meanwhile, MOC adjusts the time step sizes of those fractional cells since the numerical time step for each cell is dependent on the grid size. It is shown that MOC yields results which are compatible with data generated by the FDTD technique [11] and in good agreement with the theoretical values when EM fields reflected from a traveling and/or vibrating perfect surface [12]. Also, MOC produces reasonable trends in the following cases: the effects of medium conductivity on the propagation of EM pulse onto conducting dielectric half space [13] and the propagation of EM pulse through lossless non-uniform dielectric slab [14].…”
Section: Introductionsupporting
confidence: 63%
“…Meanwhile, MOC adjusts the time step sizes of those fractional cells since the numerical time step for each cell is dependent on the grid size. It is shown that MOC yields results which are compatible with data generated by the FDTD technique [11] and in good agreement with the theoretical values when EM fields reflected from a traveling and/or vibrating perfect surface [12]. Also, MOC produces reasonable trends in the following cases: the effects of medium conductivity on the propagation of EM pulse onto conducting dielectric half space [13] and the propagation of EM pulse through lossless non-uniform dielectric slab [14].…”
Section: Introductionsupporting
confidence: 63%
“…Shang employed it to solve the timedomain Maxwell's equations [15] through an application of explicit central-difference scheme for spatial and temporal derivatives. Its implicit formulation was developed for the same purpose and its results were found to agree with data produced by FDTD [16]. It is also shown that the characteristic-based method can predict the reflection of electromagnetic fields from moving/vibrating perfect conductor in one dimension [17,18], the effects of finite conductivity on the reflection/transmission of electromagnetic fields [19], and the reflection/transmission of electromagnetic field propagation onto moving dielectric half space [20].…”
Section: Introductionmentioning
confidence: 82%
“…Shang solves the time-domain Maxwell's equations by using the explicit finite-difference formulation in MOC in the early of 90s [5]. By elaborating with lower-upper approximate factorization method, the implicit formulation was developed for the direct time domain computation of the Maxwell curl equations and found in good agreement with results generated by FDTD [6]. Different from the MoM and FDTD approach where field components are allocated in different nodes, the characteristic-based method positions all field variables in the grid cell center.…”
Section: Introductionmentioning
confidence: 95%